The Financial Health of Mental Health Professionals - Sonya L. Britt; Bradley Klontz; Racquel Tibbetts; Linda Leitz (Journal of Financial Therapy, 2015)
Recent research has suggested that mental health professionals may be at greater risk of endorsing money scripts associated with lower income, lower net worth, and problematic financial behaviors. This study more closely examined the financial health of mental health professionals using the Klontz-Britt Financial Health Scale (FHS). Data was collected from 264 individuals recruited through financial seminars given by the researchers and through social media. Results indicated that when compared to other occupations, mental health professionals report significantly lower levels of financial health. Regardless of occupation, money status and money worship scripts were associated with lower levels of financial health, while money vigilance scripts were associated with higher levels of financial health. These results are of interest to financial counselors and educators to inform their work with those in the mental health profession who may be at greater risk of lower financial health.
Keywords: financial health; money scripts; money disorders; occupation; mental health professionals